The Role of Mentoring in the Prediction of Strategic Independence (Journal of Organizational Psychology, 2020)
This study focuses on positive dispositional traits and mentoring in the study of strategic independence among young adults. Strategic independence is a composite trait comprised used to assess a person’s propensity to make and persevere with long-term plans. Using hierarchical regression analysis on survey data collected from 324 young adults in the United States, we found that effective mentoring relationships have a positive influence on the level of strategic independence among mentees. Implications for theory and practice, limitations, and future research are discussed.
Keywords: Organizational Psychology; Traits; Strategic Independence; Mentoring; hierarchical regression analysis; United States